A Geochronological and Thermobarometric Investigation of Eclogites and overlying Hyllestad Schists from the Southern Western Gneiss Complex, Norway - Makin, Sean W. (Curtin University, 2021)
This thesis produced new pressure–temperature–time constraints on the 4D evolution of the southern Western Gneiss Complex (WGC) and overlying rocks, confirming that the Nordfjord–Sogn detachment (NSD) played a key role in developing their present-day positions. This coupled with data from further north lending weight to the WGC exhuming from flat-slab conditions. Recognition of large amounts of mechanical heating surrounding the NSD was key, with potential implications to large-scale crustal structures.